Who is the ultimate boss of legislators: Voters, special interest groups or parties? - David Stadelmann; Gustavo Torrens (ZBW - Leibniz Information Centre for Economics, 2020)
Politicians have multiple principals. We investigate the weights that politicians put on the revealed preferences of their constituents, special interest groups and party when deciding on legislative proposals. Preferences of constituents, special interest groups and parties are directly observed in our setting and they are positively correlated among each other. The empirical findings suggest that constituent preferences are assigned the lowest weight. Holding constant the preferences of other principals, constituent preferences are assigned a weight of only 10.0%. Party preferences are assigned the highest weight of all principals and special interest groups lie in between. A politician's personal ideology plays no substantial role in legislative decisions. We explore conflict among principals as well as heterogeneity among politicians. Our results cast doubt on the empirical relevance of the median voter model and suggest that more principals need to be considered to explain legislative decisions.
Keywords: D72; D78; 330; Principal-agent; multiple principals; voting; political representation; behavior of politicians